Real-time Home Bell Notification Using Node-MCU Through E-mail (Base on the Internet of Things). Issue 1 (March 2021) - Setiawan, A; Suprapto, Y; Fachrurrozi, M I; Manab, K R N; Sasmita, N R; Diyasa, G S M
Abstract: In the conventional use of the house bell, the first impression that arises is that it can only give a message ringing people who are in the house so that the person knows that guests are coming to the house, what will be the problem is what if there is no one in the house or the owner. Home away from home for a long time, so that any guests who come will not be detected. For this reason, a system is needed to make it easier for homeowners to provide message information that there are visitors to the house at some time which can be recorded on the device (notification bell) based on Internet of Things (IoT) and send the information via e-mail. This research was designed using internet-based Node-MCU as the hardware. It used a flowchart which contains procedures for how the doorbell notification device works and realtime time measurement using phpmailer as the software. The results of this study, in the form of a doorbell notification tool that can provide realtime messages to homeowners when there are known or unknown visitors.